Evolution of SUMO Function and Chain Formation in Insects - Ureña, Enric (Mol Biol Evol, 2016)
SUMOylation, the covalent binding of Small Ubiquitin-like Modifier (SUMO) to target proteins, is a posttranslational modification that regulates critical cellular processes in eukaryotes. In insects, SUMOylation has been studied in holometabolous species, particularly in the dipteran Drosophila melanogaster, which contains a single SUMO gene (smt3). This has led to the assumption that insects contain a single SUMO gene. However, the analysis of insect genomes shows that basal insects contain two SUMO genes, orthologous to vertebrate SUMO1 and SUMO2/3. Our phylogenetical analysis reveals that the SUMO gene has been duplicated giving rise to SUMO1 and SUMO2/3 families early in Metazoan evolution, and that later in insect evolution the SUMO1 gene has been lost after the Hymenoptera divergence. To explore the consequences of this loss, we have examined the characteristics and different biological functions of the two SUMO genes (SUMO1 and SUMO3) in the hemimetabolous cockroach Blattella germanica and compared them with those of Drosophila Smt3. Here, we show that the metamorphic role of the SUMO genes is evolutionary conserved in insects, although there has been a regulatory switch from SUMO1 in basal insects to SUMO3 in more derived ones. We also show that, unlike vertebrates, insect SUMO3 proteins cannot form polySUMO chains due to the loss of critical lysine residues within the N-terminal part of the protein. Furthermore, the formation of polySUMO chains by expression of ectopic human SUMO3 has a deleterious effect in Drosophila. These findings contribute to the understanding of the functional consequences of the evolution of SUMO genes.